(untitled) - Collinge, Robert A. (Upper Saddle River, NJ, 1997)
Using a unique modular format, this up-to-date survey emphasizes current issues and core economic principles. Key Topics: Offering a global orientation throughout, this book focuses on modern topics e.g., game theory, public choice, and the aggregate demand-aggregate supply model. Market: For practicing and studying economists interested in an applications- and issues-oriented approach to economics.
Keywords: Economics,Kinh tế học